Do Commonly Recommended Preventive Actions Deter Identity Theft Victimization? Findings from NCVS Identity Theft Surveys - Hu, Xiaochen (Journal of crime and justice, 2023)
It remains unknown if taking commonly used preventive actions is related to identity theft. In the current study, we use a dataset featuring over 220,000 respondents to the National Crime Victimization Survey Identity Theft Supplement (NCVS ITS). The survey was conducted by the Bureau of Justice Statistics (BJS) first in 2012, then again in 2014, and once more in 2016. The findings reported here suggest that demographic variables (e.g., gender, income) and types of online activities (e.g., frequency of online shopping) are significantly related to identity theft victimization. An interesting additional finding is that among seven distinct types of preventive actions listed in the NCVS ITS survey (frequently checking credit reports, frequently changing passwords for financial accounts, employing purchase credit monitoring, shredding documents containing personal information, monitoring bank statements for suspect charges, using security software programs, and purchasing identity theft protection), shredding documents with personal information ALONE is significantly negatively related to identity theft victimization. All six other preventive actions are either positively related or unrelated to identity theft victimization. These findings generate practical implications and, most importantly, raise the question of whether some newly-fashioned preventive actions might provide better protection from identity theft protection.